2015
DOI: 10.4085/1062-6050-50.11.02
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Examination of Adolescent Health-Related Quality of Life at 1 Year Postconcussion

Abstract: Context: Moderate to severe traumatic brain injuries can negatively influence health-related quality of life (HRQOL) in adolescent patients. The effect of sport-related concussion on adolescent HRQOL remains unclear.Objective: To investigate the perceptions of adolescent student-athletes and their parents regarding the adolescents' HRQOL 1 year after sport-related concussion.Design: Qualitative study. Setting: Secondary school.Patients or Other Participants: Seven adolescent studentathletes (age range, 12-16 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 35 publications
11
42
0
Order By: Relevance
“…In addition to interference with school, adolescents reported that the symptoms interfered with other aspects of their lives. Consistent with previous research, the symptoms have been shown to limit participation in physical and social activities (Iadevaia, Roiger, & Zwart, ; Valovich McLeod, Wagner, & Bacon, ). In other studies, adolescents have reported that they wanted to return to activities as soon as possible because social interactions are an important part of their lives (Colver & Longwell, ).…”
Section: Discussionsupporting
confidence: 86%
“…In addition to interference with school, adolescents reported that the symptoms interfered with other aspects of their lives. Consistent with previous research, the symptoms have been shown to limit participation in physical and social activities (Iadevaia, Roiger, & Zwart, ; Valovich McLeod, Wagner, & Bacon, ). In other studies, adolescents have reported that they wanted to return to activities as soon as possible because social interactions are an important part of their lives (Colver & Longwell, ).…”
Section: Discussionsupporting
confidence: 86%
“…Recent qualitative studies examining recovery have described the removal of patients following concussion from their daily social interactions along with the sudden decrease in aerobic fitness may negatively affect their quality of life. 20,21 Early aerobic exercise, even while the patient is symptomatic, may help to decrease some of these sudden changes while improving the overall mood state of the individual 22 and potentially reducing the risk of prolonged recovery. 14 However, clinician supervision is essential in early controlled aerobic exercise to ensure the initiation of activity does not exacerbate symptoms and patients participate at a subsymptom threshold.…”
Section: Resultsmentioning
confidence: 99%
“…The consequence is that people with mTBI may hear mixed messages, becoming confused and potentially losing confidence in care providers. 61,62 OVERCOMING KNOWLEDGE BARRIERS Sports concussion and athletic training professions benefit from regular updates to published guidelines; documents are developed specifically for dissemination to practitioners with the intent of providing concise literature updates to inform clinical practice. Sports concussion guidelines were last updated in 2017 50 and guidelines for athletic training in 2014.…”
Section: Flexible Updates: Balancing Rest and Activity After Mtbimentioning
confidence: 99%